2007
DOI: 10.1080/07315724.2007.10719612
|View full text |Cite
|
Sign up to set email alerts
|

Fish and Fat Intake and Prevalence of Allergic Rhinitis in Japanese Females: the Osaka Maternal and Child Health Study

Abstract: Our findings suggest that the intake of eicosapentaenoic and docosahexaenoic acids may be associated with a reduced prevalence of allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 38 publications
1
31
1
Order By: Relevance
“…Gender-specific effects as observed in the present study have been reported previously [50][51][52] . The reason for this difference is not clear, but it might be possible that it is due to gender-specific differences in the metabolism of n-3 fatty acids.…”
Section: Discussionsupporting
confidence: 86%
“…Gender-specific effects as observed in the present study have been reported previously [50][51][52] . The reason for this difference is not clear, but it might be possible that it is due to gender-specific differences in the metabolism of n-3 fatty acids.…”
Section: Discussionsupporting
confidence: 86%
“…Diet may influence both inflammatory and allergic diseases in general, but the role of diet particularly in rhinitis and sinusitis is not clearly understood although a few studies have been reported on the association between dietary factors and allergic type of rhinitis (De Batlle J et al 2008, Farchi S et al 2003, Huang SL et al 2001, Hoff S et al 2005, Miyake Y et al 2007). The mixed condition of allergic and non-allergic types is most common in rhinitis (Dykewicz MS and Hamilos DL 2010,Wallace DV et al 2008, Settipane RA and Charnock DR 2007, and sinusitis frequently occurs with rhinitis (Tan RA and Corren J 2011, Dykewicz MS and Hamilos DL 2010, Van Crombruggen K et al 2011, Meltzer EO et al 2004).…”
Section: ⅳ Discussion and Conclusionmentioning
confidence: 99%
“…In the study with adolescents, the frequent consumption of animal liver and fruits were associated with an increased risk of allergic rhinitis (Huang SL et al 2001). In the study with adults, high intakes of alpha-linolenic, eicosapentaenoic, and docosahexaenoic acids were associated with a decreased risk of allergic rhinitis (Hoff S et al 2005, Miyake Y et al 2007). There has been an inconsistency in the association of milk consumption and allergic rhinitis; one study showed an inverse association (Farchi S et al 2003), but the other showed a positive association (Huang SL et al 2001).…”
Section: Introduction 1)mentioning
confidence: 92%
“…Similarly, individuals allergic to shellfish are advised to avoid crustacean and/or molluscan shellfish, due to the high cross-reactivity among shellfish species. On the other hand, seafood is a source of polyunsaturated fatty acids that could modulate an inflammatory response in many diseases, including allergic disorders; therefore, a diet without fish and shellfish in order to reduce contact with respective seafood allergens and A. simplex allergens should be carefully balanced [78][79][80].…”
Section: Seafood Hypersensitivity and Toxicitymentioning
confidence: 99%